(untitled) (Journal of Human Sciences, 2021)
This study aims to shed light on the city of Murzuq in the Fezzan region during the nineteenth century, and its important role in the desert transit trade, as the city of Murzuq, by virtue of its geographical location, was of great importance in its spirit as a pivotal city in the intra-trade between northern Libya and the countries of sub-Saharan Africa. It was in the middle of the Libyan desert, and its important location on the desert road that passes through it from Tripoli to the Kingdom of Yarno and the Central Sudan. This study deals with the city of Murzuq and its pivotal role in the commercial desert caravan trade in the Fezzan region, and how Murzuq turned into a bustling and prosperous city with trade in the nineteenth century thanks to the desert caravan trade, and thanks to the city’s important location in the middle of the Libyan desert. One of the reasons for the researcher’s choice of this topic is that the desert transit trade through Murzuq is what made the city of economic and political importance more than anything else, and therefore the researcher believes that the city of Murzuq and its economic importance in the nineteenth century did not give rise to its abundant right of study and analysis, and accordingly the researcher will use The historical, narrative and analytical approach in its study.